A web-based pilot randomized controlled trial to test the efficacy of education and contact-based interventions in reducing public suicide stigma - Nathalie Oexle; Matthias Lühr; Daniele Valacchi; Nicolas Rüsch (BMC Psychiatry)
Abstract Background Interventions to reduce public suicide stigma (i.e. negative attitudes towards persons affected by suicide/suicidality) could contribute to suicide prevention. However, such interventions could unintentionally increase suicide normalization (i.e. liberal attitudes towards suicide) and therefore increase suicide risk. We aimed to test the efficacy of education- and contact-based interventions delivered online via video or text on both public suicide stigma and suicide normalization. Methods We conducted a web-based randomized controlled trial among N = 2,043 participants recruited from an established online research panel. Participants were randomized into six groups, receiving either one of four contact- or education-based interventions that were transferred via text or video (contact text, contact video, education text, education video) or control group content (contact control, education control). Information about suicide stigma and suicide normalization were collected directly before (t0) and after intervention participation (t1) as well as about two weeks later (t2). To explore the attractiveness of the provided intervention material, we used Brown-Mood’s median test to compare the times participants spent with the provided intervention material in each group. We then used linear mixed models to compare effects on suicide stigma and suicide normalization between intervention groups and control groups. Results Median times spent with provided material were generally longer among participants exposed to video material than among participants exposed to text material, and among participants in contact-based interventions than among participants in education-based interventions. We did not observe stronger effects in intervention groups compared to control groups on suicide stigma or suicide normalization. Surprisingly, suicide stigma and suicide normalization appeared to decrease from t0 to t1 in both intervention and control groups. Conclusion Our findings suggest a higher attractiveness of video- and contact-based material compared to text- and education-based material. However, none of the interventions had a significant effect on public suicide stigma or suicide normalization. Future research should explore innovative and safe approaches to reduce public suicide stigma. Experimental studies may focus on interventions with higher attractiveness (i.e. video and contact-based interventions), use interventions with higher intensity (i.e. longer interventions, more repetitions), and assess suicide stigma with implicit measures to avoid response bias. Trial registration The RCT was registered at clinicaltrials.gov on February 11th, 2021 (NCT04756219).